The Mediatization of Socially Important Issues and the Dynamics of Civil Society - Bolshakov, Sergey Nikolaevich; Mikhalchenkova, Natalya Alekseevna; Istikhovsaya, Marina Dmitrievna; Bolshakova, Yulia Mikhalovna (International Review of Management and Marketing, 2015)
The article analyzes the complex nature of media design of socially important issues. The author observes the complexity of today's social organization, its differentiation in the socio-economic, political, and cultural-stylistic aspects. The main purpose of the article is to examine the role and influence of the mass media on the processes of agenda-building and formation of civic mindedness in society, as well as to assess the complexity of media design of socially important issues. The author summarizes the dynamics of civic self-organization in the course of collective definition of socially important topics and reveals the significant role of the mass media in their collective representation and elaboration of the ways to resolve them. Author clues the importance of multivariance and unpredictability of the processes of social and political self-organization of citizens in the course of design of socially important issues of present-day society. Keywords: socially important issue, mobilization of society, communication technologies, mass media, civil society, policy JEL Classifications: Z13; Z18